2022
DOI: 10.3390/molecules27123701
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Properties against SARS-CoV-2 of Epoxybenzooxocino[4,3-b]Pyridine Derivatives

Abstract: The COVID-19 pandemic is ongoing as of mid-2022 and requires the development of new therapeutic drugs, because the existing clinically approved drugs are limited. In this work, seven derivatives of epoxybenzooxocinopyridine were synthesized and tested for the ability to inhibit the replication of the SARS-CoV-2 virus in cell cultures. Among the described compounds, six were not able to suppress the SARS-CoV-2 virus’ replication. One compound, which is a derivative of epoxybenzooxocinopyridine with an attached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Gilead Sciences researchers discovered that adenosine C-nucleoside with 1'-CN modification had potent anti-Ebola virus action in Hela cells and human umbilical vein endothelial cells. Remdesivir is the name of this potent substance (9). A nucleoside analogue called remdesivir (GS-5734; Gilead Sciences Inc., USA) functions as a competitive inhibitor of viral RNA-dependent RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…Gilead Sciences researchers discovered that adenosine C-nucleoside with 1'-CN modification had potent anti-Ebola virus action in Hela cells and human umbilical vein endothelial cells. Remdesivir is the name of this potent substance (9). A nucleoside analogue called remdesivir (GS-5734; Gilead Sciences Inc., USA) functions as a competitive inhibitor of viral RNA-dependent RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also tested modified 5H-5,11-epoxybenzo [7,8]oxocino [4,3b]pyridine 3a derivatives for antiviral and bacteriostatic activity [24,25]. One of the synthesized compounds demonstrated high cytotoxicity and clear inhibition of the SARS-CoV-2 virus replication [24]. At the same time, a number of synthesized oxocino [4,3-b]pyridine derivatives 3a showed pronounced and average anti-tuberculosis activity along with moderate antibacterial and antifungal activity [25].…”
Section: Synlettmentioning
confidence: 99%
“…This allows us to suppose the antiviral potential of the previously obtained epoxybenzo [7,8]oxocino [4,3-b]pyridine derivatives as synthetic analogues of natural integrastatins A, B. In addition, we also tested modified 5H-5,11-epoxybenzo [7,8]oxocino [4,3b]pyridine 3a derivatives for antiviral and bacteriostatic activity [24,25]. One of the synthesized compounds demonstrated high cytotoxicity and clear inhibition of the SARS-CoV-2 virus replication [24].…”
Section: Synlettmentioning
confidence: 99%
See 1 more Smart Citation
“…Epoxybenzo[7,8]oxocino[4,3- b ]pyridine derivatives were synthesized and tested for antiviral and bacteriostatic activities in our previous works. 14 15 One of the synthesized compounds demonstrated high cytotoxicity and pronounced inhibition of SARS-CoV-2 viral replication. It was also shown that a series of synthesized oxocino[4,3- b ]pyridine derivatives perform pronounced and moderate antituberculous activity along with moderate antibacterial and antifungal activity.…”
Section: Synthesismentioning
confidence: 99%